Smart mobile application for short-haul cargo transportation - Ahmed Azab; Jaehyun Park; Noha A. Mostafa (Logistics, 2021)
Smart service systems have been dealing with various wicked social and cultural problems by providing diverse solutions for society. Cargo transportation is one of the most challenging issues in logistics; in this paper, we explore multiple stakeholders' information environments surrounding containerized cargo transportation by a design thinking approach. Throughout the analysis, the latent problems are summarized in the following two manners: (1) miscommunication with inefficient information flow among multiple stakeholders; and (2) a lack of resource management coordination among service providers. With these two identified problems, the objective of this work is to develop a prototype information and communication technology-based service application for both trucking companies and customers. This work makes two contributions. First, it methodologically proposes a customer-centered design approach for logistics management by adopting a design thinking approach. Second, it suggests a practical ICT-based solution for the mentioned problems.
Keywords: 650; containerized truck transport; service science; smart service systems; design thinking; smart mobile application